Stylized Facts and International Business Cycles - The German Case - Michael Gail (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1998)
This paper studies the business cycle in Germany using the HP-filter (Hodrick/Prescott (1997)) to isolate the cyclical component. A two-country International Business Cycle model in line with Baxter/Crucini (1995) is built to explain these facts. The combination of GHH-preferences with taste shocks resulting from government consumption is shown to be an important feature of the German business cycle. A VAR model for the exogenous variables is estimated that enables the model not only to account well for the observed positive international correlations of outputs, consumptions and savings but also for their lead-lag relationship. Hours worked and investments are positively correlated in this model - a property not realized in other single-good models of the International Business Cycle in the literature.
Keywords: E32; F41; 330; International Real Business Cycles; Stylized Facts; GHH-preferences; Konjunktur; Real Business Cycle; Konjunkturzusammenhang; Schätzung; Deutschland; USA